Variability in exercise capacity and metabolic response during endurance exercise after a low carbohydrate diet - Claassen, A.; Lambert, E. V.; Bosch, A. N.; Rodger, I. M.; St. Clair Gibson, A.; Noakes, T. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The impact of altered blood glucose concentrations on exercise metabolism and performance after a low carbohydrate (CHO) diet was investigated. In random order, 1 wk apart, 9 trained men underwent euglycemic (CI) or placebo (PI) clamps, while performing up to 150 min of cycling at 70% VO2(max), after 48 h on a low CHO diet. The range in improvement in endurance capacity with glucose infusion was large (28 +/- 26%, P < 0.05). Fifty-six percent of subjects in CI failed to complete 150 min of exercise despite maintenance of euglycemia, while only 2 subjects in PI completed 150 min of exercise, despite being hypoglycemic. Total CHO oxidation remained similar between trials. Despite longer exercise times in CI, similar amounts of muscle glycogen were used to PI. Maintenance of euglycemia in the CHO-depleted state might have an ergogenic effect, however, the effect is highly variable between individuals and independent of changes in CHO oxidation.